2021
DOI: 10.1097/ccm.0000000000005069
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Hyperoxia and Neurologic Outcomes in Patients Undergoing Extracorporeal Membrane Oxygenation

Abstract: OBJECTIVES: To evaluate the impact of duration of hyperoxia on neurologic outcome and mortality in patients undergoing venoarterial extracorporeal membrane oxygenation. DESIGN: A retrospective analysis of venoarterial extracorporeal membrane oxygenation patients admitted to the Johns Hopkins Hospital. The primary outcome was neurologic function at discharge defined by modified Rankin Scale, with a score of 0–3 defined as a good neurologic outcome, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 21 publications
(26 reference statements)
3
46
0
Order By: Relevance
“…Our study suggests that severe degrees of hyperoxemia (PaO 2 >200 mmHg) during the early stages of VA ECMO support is also very common. This is consistent with prior studies in ECMO patients ( 4 , 5 , 16 , 17 ). VA ECMO patients are critically unwell and reluctance among physicians in making too many early changes may also contribute to severe hyperoxemia during the early stages of VA ECMO support.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study suggests that severe degrees of hyperoxemia (PaO 2 >200 mmHg) during the early stages of VA ECMO support is also very common. This is consistent with prior studies in ECMO patients ( 4 , 5 , 16 , 17 ). VA ECMO patients are critically unwell and reluctance among physicians in making too many early changes may also contribute to severe hyperoxemia during the early stages of VA ECMO support.…”
Section: Discussionsupporting
confidence: 93%
“…Our study finding is in contrast with multiple studies suggesting hyperoxemia is associated with increased mortality in VA ECMO supported patients. Al-Kawaz et al ( 17 ) in a single center study reported that duration and severity of early hyperoxemia were independently associated with poor neurologic outcomes at discharge as well as with mortality. However, Munshi et al ( 5 ) reported potential harm associated with hyperoxemia in venovenous ECMO patients and in those receiving VA ECMO in the context of cardiopulmonary resuscitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When patients with poor cardiac function received VA ECMO, the brain is oxygenated by extracirculatory gas exchange. For patients on both VA and VV ECMO, early hyperoxia (within 24 h after ECMO onset) is significantly associated with higher mortality (84,85). Furthermore, early hyperoxia increases the risk of acute brain injury and unfavorable neurologic outcomes (84).…”
Section: Preventionmentioning
confidence: 99%
“…For patients on both VA and VV ECMO, early hyperoxia (within 24 h after ECMO onset) is significantly associated with higher mortality (84,85). Furthermore, early hyperoxia increases the risk of acute brain injury and unfavorable neurologic outcomes (84). However, the most appropriate strategy and correction target for PaO 2 and PaCO 2 in patients undergoing ECMO remain uncertain and need to be further studied.…”
Section: Preventionmentioning
confidence: 99%